EFFECT OF PROGRESSIVE MOBILIZATION ON BLOOD PRESSURE CHANGES IN STROKE PATIENTS IN ICU ROOM - Suwarly Mobiliu; Mansur Tomayahu (Universitas Negeri Gorontalo, 2021)
Stroke is one of the cases that require hemodynamic monitoring and is a significant health problem for today's modern society. This condition often occurs where the blood supply to a part of the brain is suddenly interrupted, due to blockage or rupture of a blood vessel in the brain. The American Association of Critical-Care Nurses (AACN) introduces progressive mobilization interventions (Head of Bed, Range of Motion, and continued rotation). Laterals). Progressive mobilization is expected to cause an excellent hemodynamic response. This study aims to determine the effect of progressive mobilization on changes in blood pressure in stroke patients in the ICU MM Dunda Limboto Hospital. This type of research is a quasi-experimental approach with a pre and post-test design group approach. The number of respondents was 15 people with an accidental sampling technique. The analysis results showed that there were differences in blood pressure results before and after progressive mobilization, with the bivariate analysis results with the Wilcoxon test 0.000 0.05, which means that giving progressive mobilization to stroke patients affects changes in blood pressure. The conclusion is that there is an effect of giving progressive mobilization to decrease blood pressure of stroke patients in the ICU MM Dunda Limboto Hospital.